Removal of Thallium(I) Using Saffron as Complexing Agent - NAGHIZADEH, M.; AFZALI, M. (Asian Journal of Chemistry, 2010)
In this work, the potential of saffron for complex formation with thallium(I) is investigated. The saffron was adsorbed onto XAD-4 Amberlite resin and then passed the sample solution containing Tl+ through it. Tl+ can be remained on the modified resin in the pH range of 3.5-7.5. The solution was examined before and after passing through saffron adsorbed XAD-4 resins and finally the concentration of Tl+ were determined by flame atomic absorption spectrometry. The concentration of Tl+ is found very low after passed through the resin. These results were compared with a column containing unmodified XAD-4 resin which showed that unmodified XAD-4 resin don’t retain Tl+. Therefore, saffron can be complex with Tl+ in the pH range of 3.5-7.5. The analytical potential of saffron adsorbed onto XAD-4 Amberlite resin for the removal of Tl+ from the biological body was also performed.